Cisco CCNP security SCOR (Exam 350-701) - Sequeira, Anthony; Wong, Ronnie (Packt Publishing, 2024)
The course begins with a thorough exploration of network threats, vulnerabilities, and their mitigations, providing a solid foundation in cybersecurity. It dives into the specifics of on-prem and cloud threats, emphasizing common security vulnerabilities and attack mitigation strategies. The course also covers the essentials of cryptography, including modern cryptographic solutions and the fundamentals of Public Key Infrastructure (PKI). The course focuses on practical skills, exploring various Cisco security tools and techniques. It delves into network security deployment models, NetFlow, network segmentation, and advanced security protocols like IKEv1 and IKEv2. The course also covers the use of Python scripts for enhancing security appliance API calls and differentiates between intrusion prevention and firewalling. The course wraps up with detailed insights into Cisco's security products, including Firepower devices, Web Proxy, ESA, WSA, and Cisco Umbrella. It provides practical knowledge on configuring and verifying these tools, alongside addressing endpoint security, Multi-Factor Authentication (MFA), and device compliance. What you will learn Identify and mitigate network threats Implement on-prem and cloud security Understand modern cryptographic solutions Utilize Python for security automation Configure Cisco Firepower and Umbrella Manage network security with Cisco tools Audience This course is ideal for any learner who wants to understand enterprise-level approaches to defense in depth security of systems and data. This course targets implementers and lead architects of security solutions with a bias toward the use of Cisco security hardware and software releases. From a certification perspective, this course prepares learners to pass exam 350-701 (SCOR). About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Anthony Sequeira: Anthony Sequeira, CCIE #15626, is a seasoned tech trainer and author with expertise in cloud, cybersecurity, and IT. His IT journey began in 1994 at IBM in Tampa, Florida. He later founded Computer Solutions but discovered his true passion for teaching and writing about technology. In 1996, he joined Mastering Computers, which evolved into KnowledgeNet, where he continued to share the latest tech advancements. Today, he serves as a full-time Edutainer at ACI Learning, delivering global training and authoring textbooks on modern technologies. He holds certifications like CCIE R&S #15626, as well as numerous others from AWS, CompTIA, Juniper, and Microsoft, among others. Anthony's expertise spans the IT landscape. Ronnie Wong: Ronnie Wong has had a diverse career, from diesel service and ministry to computer repair and network administration in small businesses. He set up networks and servers and created policies in these roles. As an Edutainer at ITProTV, now ACI Learning, he started as an IT technical instructor, later working as a contract trainer for the University of Florida, Marion County School Systems, and Nationwide Insurance. He provided Cisco, Microsoft Windows, CompTIA, and IT security training to military and DoD personnel. Now the Director of Content Development at ACI Learning, Ronnie's credentials include CCNP Enterprise Infrastructure, CCNA, CompTIA's A+, Network+, Security+, ISC2 CC, CNA Security, and PCNSA.
Online resource; title from title details screen (O'Reilly, viewed January 30, 2024)
Keywords: Cisco Systems, Inc -- Study guides -- Examinations; Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet